Pengaruh Kompetensi dan Faktor Lainnya Terhadap Kinerja Karyawan F&B PT. ABC - Susanto, Aryana; Ananda, Denta (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this study is to determine and analyze the influence of competence, career development, and organizational culture on employee performance at PT. ABC. The population in this study were all employees of PT. ABC, totaling 90 individuals. The sampling technique used in this research is non-probability sampling with a saturated sampling method. Data were collected by distributing questionnaires to respondents using a Likert scale. The data analysis method applied is multiple linear regression. Before testing the hypothesis, data analysis was conducted, including instrument testing, classical assumption testing, and model testing using statistical software. The results of hypothesis testing in this study indicate that competence has a positive effect on employee performance, career development has a positive and effect on employee performance, and organizational culture has a positive and effect on employee performance.